Analisa Risiko Postur Tubuh Pekerja dengan Metode NBM, REBA dan RULA di Unit Usaha Jamur Tiram Putih Fungo Pride - turseno, andi; Marcaesa, Gita (Journal of Industrial and Engineering System, 2021)
Fungo Pride is a business unit engaged in the cultivation of white oyster mushrooms. Unhealthy environmental conditions and work stations certainly create a work environment that is less comfortable, unsafe, unhealthy and inefficient. So that the condition of the work station can reduce performance and cause risks. This study aims to analyze the work risks of the Fungo Pride Business Unit associated with non-ergonomic work positions using the NBM, REBA & RULA methods. From the results of this study, it was found that the NBM analysis found 50% low risk and 50% moderate risk. For REBA analysis, it is found that the work risk of employees is in a very high category with a final REBA score of 13 so it requires corrective action as soon as possible. And based on the RULA analysis, the results were in the very high category, namely the grand score of RULA 8, so it is necessary to have an investigation and repair as soon as possible. With the results of these studies, it is hoped that there will be further research that discusses ergonomic factors with productivity in the oyster mushroom cultivation business unit.